2019
DOI: 10.1182/blood-2018-11-844548
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil plasticity in the tumor microenvironment

Abstract: Neutrophils act as the body’s first line of defense against infection and respond to diverse inflammatory cues, including cancer. Neutrophils display plasticity, with the ability to adapt their function in different inflammatory contexts. In the tumor microenvironment, neutrophils have varied functions and have been classified using different terms, including N1/N2 neutrophils, tumor-associated neutrophils, and polymorphonuclear neutrophil myeloid–derived suppressor cells (PMN-MDSCs). These populations of neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
419
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(437 citation statements)
references
References 97 publications
13
419
0
5
Order By: Relevance
“…A number of neutrophil subpopulations have previously been identified through functional and phenotypic associations in various models, including but are not limited to human CD177 + (Hu et al, 2009;Silvestre-Roig et al, 2016;Wu et al, 2016;Zhou et al, 2018), olfactomedin-4 + (OLFM4) (Clemmensen et al, 2012), TCR-expressing (Puellmann et al, 2006), CD49d + VEGFR1 high CXCR4 high angiogenic (Christoffersson et al, 2012;Massena et al, 2015), CD63 + (Tirouvanziam et al, 2008), IL-13 + (Chen et al, 2014), CD49 + (Cheung et al, 2010;Tsuda et al, 2004), IL-17producing (Taylor et al, 2014), CD62L dim /CD16 bright and CD62L bright /CD16 dim (Pillay et al, 2012), immunosuppressive CD11c bright CD62L dim CD11b bright CD16 bright (Pillay et al, 2012), CD16 dim banded (Leliefeld et al, 2018), CD62L dim (Tak et al, 2017), mature CD10 + and immature CD10 - (Marini et al, 2017), and tumor- Neutrophils are now known to be important in cancer. Two tumor-associated neutrophil (TAN) subpopulations are present in tumors: pro-inflammatory antitumorigenic N1 neutrophils and pro-tumorigenic N2 neutrophils (Fridlender et al, 2009;Giese et al, 2019;Sionov et al, 2015). N1 TANs showed a more immunostimulatory mRNA profile than N2 neutrophils, expressing higher levels of TNF-α, CCL3, iNOS, and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…A number of neutrophil subpopulations have previously been identified through functional and phenotypic associations in various models, including but are not limited to human CD177 + (Hu et al, 2009;Silvestre-Roig et al, 2016;Wu et al, 2016;Zhou et al, 2018), olfactomedin-4 + (OLFM4) (Clemmensen et al, 2012), TCR-expressing (Puellmann et al, 2006), CD49d + VEGFR1 high CXCR4 high angiogenic (Christoffersson et al, 2012;Massena et al, 2015), CD63 + (Tirouvanziam et al, 2008), IL-13 + (Chen et al, 2014), CD49 + (Cheung et al, 2010;Tsuda et al, 2004), IL-17producing (Taylor et al, 2014), CD62L dim /CD16 bright and CD62L bright /CD16 dim (Pillay et al, 2012), immunosuppressive CD11c bright CD62L dim CD11b bright CD16 bright (Pillay et al, 2012), CD16 dim banded (Leliefeld et al, 2018), CD62L dim (Tak et al, 2017), mature CD10 + and immature CD10 - (Marini et al, 2017), and tumor- Neutrophils are now known to be important in cancer. Two tumor-associated neutrophil (TAN) subpopulations are present in tumors: pro-inflammatory antitumorigenic N1 neutrophils and pro-tumorigenic N2 neutrophils (Fridlender et al, 2009;Giese et al, 2019;Sionov et al, 2015). N1 TANs showed a more immunostimulatory mRNA profile than N2 neutrophils, expressing higher levels of TNF-α, CCL3, iNOS, and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…34,89,93 They induced angiogenesis and the recruitment of neutrophils, generally associated with poor prognosis in cancer. 94 IL-17-producing cd T cells also promoted the recruitment of immunosuppressive neutrophils and small peritoneal macrophages, which inhibit CTL response and enhance tumor growth. Nevertheless, neutrophils display phenotypical and functional plasticity depending on the tumor microenvironment, and have been found to also contribute to antitumor immune response, notably through antibody-dependent cellular cytotoxicity (ADCC) and recruitment of other immune cells.…”
Section: T Cells As Drivers Of Tumor Growthmentioning
confidence: 99%
“…Nevertheless, neutrophils display phenotypical and functional plasticity depending on the tumor microenvironment, and have been found to also contribute to antitumor immune response, notably through antibody-dependent cellular cytotoxicity (ADCC) and recruitment of other immune cells. 94 IL-17-producing cd T cells also promoted the recruitment of immunosuppressive neutrophils and small peritoneal macrophages, which inhibit CTL response and enhance tumor growth. 34,88,90,93 In a model of pancreatic ductal adenocarcinoma (PDA), IL-17 + IL-10 + cd T cells were also directly suppressive of T-cell responses.…”
Section: T Cells As Drivers Of Tumor Growthmentioning
confidence: 99%
“…Neutrophil heterogeneity has become an active research area, particularly with regards to cancer progression. 17 Comprehensive examination by flow cytometry has revealed that neutrophils express a complex surface antigen profile. 27 However, due to the limitations imposed by flow cytometry, researchers have had to arbitrarily select only a few surface markers to examine at a particular time.…”
Section: Discussionmentioning
confidence: 99%
“…16 Interestingly, work in this field has also suggested differential involvement of neutrophil subpopulations in cancer. 17,18 Thus, the development of neutrophil consensus markers is required for improving our understanding of neutrophil biology and its relationship to disease progression.…”
Section: Introductionmentioning
confidence: 99%